Image Congruity or Functional Congruity? The Moderating Effect From the Social Visibility of Hotel Consumption at Different Price Levels. (September 2019) - Su, Na; Hu, Yaou; Min, Hyounae (Kelly)
Consumers maintain a balance between functional congruity and self-image congruity when choosing a hotel brand. We argue that the way in which consumers tip the balance is related to their perception on how socially visible or invisible their consumption of the hotel brand is. This study draws on the self-congruity theory and tests eight hotel brands in the United States. The results show that functional congruity, in general, has a greater effect than self-image congruity on the consumers' attitude toward a brand. However, the effect of self-image congruity increases with the perceived social visibility of hotel consumption, and this increase is especially salient for high-priced hotels but is not with low-priced hotels. We show that whether the consumption of the brand is socially visible or invisible is an important factor to consider when trying to understand a consumer's attitude toward a hotel brand.